1995
DOI: 10.1139/f95-120
|View full text |Cite
|
Sign up to set email alerts
|

A length-based population model and stock–recruitment relationships for red king crab, Paralithodes camtschaticus, in Bristol Bay, Alaska

Abstract: A length-based population model was constructed for Bristol Bay red king crab, Paralithodes camtschaticus, incorporating stochastic growth, gradual recruitment over length, and a bowl-shaped pattern for instantaneous natural mortality as a function of length. A nonlinear least squares approach was used to estimate abundance, recruitment, and natural mortality. The model was applied to abundance and catch data from 1968 to 1993. The observed population abundances fit well with the model. Natural mortality was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
110
0
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 14 publications
2
110
0
5
Order By: Relevance
“…Year-specific estimates of M for northern shrimp in Kachemak Bay, Alaska, showed an increasing trend through time, which may have resulted from increasing predation pressure from groundfish (Fu and Quinn 2000). Based on a review of previously published estimates, Zheng et al (1995a) concluded that M was lower for intermediate-size red king crabs than it was for smaller and larger crabs and that M varied substantially over time. Thus, they included effects of sex, size, and year on M for red king crab in a population dynamics model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Year-specific estimates of M for northern shrimp in Kachemak Bay, Alaska, showed an increasing trend through time, which may have resulted from increasing predation pressure from groundfish (Fu and Quinn 2000). Based on a review of previously published estimates, Zheng et al (1995a) concluded that M was lower for intermediate-size red king crabs than it was for smaller and larger crabs and that M varied substantially over time. Thus, they included effects of sex, size, and year on M for red king crab in a population dynamics model.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they included effects of sex, size, and year on M for red king crab in a population dynamics model. Concerns about overparameterization of the model led them to develop a more parsimonious version that removed the size dependence in M, but results were similar (Zheng et al 1995b). Siddeek et al (2002) estimated M separately for male and female king crabs, but attempts to estimate M by year were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Обозначим количество животных, погибших по естественным причинам, символом C t ,a , тогда схему эксплуатируемой популяции рыб, согласно уравнениям Виртуально-популяционный анализ динамики численности промысловых ракообразных на основе возрастных когорт не получил широкого применения в силу сложности определения точного возраста животного (ICES, 2001a;ICES, 2001б). Однако с начала 90-х годов прошлого столетия, основные принципы изменения численности поколений, разработанные Ф. И. Барановым, стали с успехом применяться в моделировании динамики численности крабов и креветок (Collie, 1991;Kruse and Collie, 1991;Zheng et al, 1995;Quinn et al, 1998;Cadrin, 2000). Модели этого типа базировались на изменениях численности не поколений, а размерных групп (LBA, length-based analysis) и учитывали линьку и стохастический рост животных.…”
Section: модели популяционной динамикиunclassified
“…Пополнение (R) моделируемой популяции камчатского краба американские исследователи описали с помощью двух параметров: 1) количество молодых крабов, пополняющих популяцию в году t, R t и 2) параметр U l , определяющий стохастическое изменение процесса пополнения (Sullivan et al, 1990;Zheng et al, 1995). Пополнение каждой размерной группы R l, t выражалось через уравнение:…”
Section: модели популяционной динамикиunclassified